SISTEM INFORMASI PERSEDIAAN BARANG DENGAN METODE FIFO PADA STMIK KRISTEN NEUMANN INDONESIA - Ina Valerina; Bersama Sinuraya (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
Processing of inventory data on the STMIK Christian Neumann Indonesia Campus is still using the manual method, Often the inventory distribution process is carried out resulting in misunderstanding. Then we need an inventory system on the STMIK Christian Neumann Indonesia Campus with the FIFO (First In First Out) method.